(untitled) (International Journal of Engineering and Computer Science, 2013)
Singular value decomposition (SVD) based algorithm is designed to compress the black and white images to evaluate the effect of information content of the image. Inorder to evaluate the effect second algorithm is developed to calculate the SNR, PSNR, MSE, and RMSE value of the compressed images with respect to reference image. It is interpreted from the results that high level of compression the information content of the image is degraded to higher level